Barriers and Facilitators to Aerobic Exercise Implementation in Stroke Rehabilitation: A Scoping Review. Issue 3 (July 2020) - Moncion, Kevin; Biasin, Louis; Jagroop, David; Bayley, Mark; Danells, Cynthia; Mansfield, Avril; Salbach, Nancy M.; Inness, Elizabeth; Tang, Ada
Abstract : Background and Purpose: Aerobic exercise is a recommended part of stroke best practices; yet, access to aerobic exercise programs within stroke rehabilitation remains limited and inconsistent. The purpose of this scoping review was to describe the nature and extent of barriers and facilitators to aerobic exercise implementation with adults post-stroke as reported by health care professionals. Methods: MEDLINE, EMBASE, Web of Science, CINAHL, PsycINFO, and AMED Allied and Complementary Medicine were searched from inception to October 16, 2019. Research studies that examined health care professionals' barriers and facilitators to aerobic exercise implementation in adults post-stroke were included. Two reviewers independently conducted title and abstract screening, full-text evaluation, data extraction, and quality appraisal. The Theoretical Domains Framework was used to map the identified barriers or facilitators and to analyze and interpret the results. Results: Four studies were included in the review. All studies involved surveys conducted among physical therapists and reported barriers related to "environmental context and resources" (eg, lack of equipment, time, staff), insufficient "knowledge" and "skills" (eg, safe aerobic exercise prescription and implementation), "beliefs about capabilities" (eg, uncertainty about exercise intensity and screening tools), and professional role and identity (eg, aerobic exercise not a priority). Access to and continued education in structured aerobic exercise programs and safety monitoring were identified facilitators. Discussion and Conclusions: Some of the identified barriers could be overcome with modeling and training in best practice, while others may require interventions targeting organizational environment and leadership. Future knowledge translation interventions should target the identified barriers and facilitators to implementing aerobic exercise. Video Abstract available for more insights from the authors (see the Video, Supplemental Digital Content 1, http://links.lww.com/JNPT/A312 ). Abstract : Supplemental Digital Content is Available in the Text.